Using a PCA-based dataset similarity measure to improve cross-corpus emotion recognition. (September 2018) - Siegert, Ingo; Böck, Ronald; Wendemuth, Andreas
Highlights: Presented a method for informed selection of similar datasets based on distribution of acoustic characteristics. Applied method for cross-corpus emotion recognition from speech using state-of-the-art approaches. Outperformed uninformed cross-corpus analyses as well as feature normalization as alternative method. Influence of various factors that could be seen as alternative explanation for improvement were excluded by various experiments. Abstract: In emotion recognition from speech, huge amounts of training material are needed for the development of classification engines. As most current corpora do not supply enough material, a combination of different datasets is advisable. Unfortunately, data recording is done differently and various emotion elicitation and emotion annotation methods are used. Therefore, a combination of corpora is usually not possible without further effort. The manuscript's aim is to answer the question which corpora are similar enough to jointly be used as training material. A corpus similarity measure based on PCA-ranked features is presented and similar datasets are identified. To evaluate our method we used nine well-known benchmark corpora and automatically identified a sub-set of six most similar datasets. To test that the identified most similar six datasets influence the classification performance, we conducted several cross-corpora emotion recognition experiments comparing our identified six most similar datasets with other combinations. Our most similar sub-set outperforms all other combinations of corpora, the combination of all nine datasets as well as feature normalization techniques. Also influencing side-effects on the recognition rate were excluded. Finally, the predictive power of our measure is shown: increasing similarity score, expressing decreasing similarity, result in decreasing recognition rates. Thus, our similarity measure answers the question which corpora should be included into joint training.